The effect of human papilloma virus vaccination on embryo yield and clinical in vitro fertilisation outcomes: a matched retrospective cohort study. (3rd April 2021) - Demir, Mustafa; Ince, Onur; Yilmaz, Bulent; Decleer, Wim; Osmanagaoglu, Kaan
Abstract: The effects of HPV vaccination on embryo yield and pregnancy outcomes in IVF cycles with fresh embryo transfer (ET) were investigated. First, embryo yielding rates (EYR) in 2795 cycles with and without HPV vaccination were compared by retrospective cohort study design. EYR of HPV vaccinated and non-vaccinated patients were not significantly different (OR, 1.66; 95% CI, 0.76–3.63). Second, ET outcomes were compared for 155 HPV vaccine + cycles and 465 HPV vaccine - cycles after matching for ages and cycle attempt number. The differences in the number of retrieved oocytes (10.2 ± 6.1, 11.2 ± 6.7; p  = .161), mature (MII) oocytes (8.7 ± 5.7, 9.8 ± 6.3; p  = .088), two pronuclear zygotes (2PN) (5.4 ± 4.1, 6.1 ± 4.6; p  = .110) and fertilisation rates (0.62 ± 0.23, 0.62 ± 0.23; p  = .539) were insignificant between the two groups. Moreover, positive (OR, 0.74; 95% CI, 0.47–1.16), clinical (0.60; 0.36–1.01) and the ongoing pregnancy (0.55; 0.30–1.01) rates were lower in the HPV vaccinated group but the difference was not statistically significant. IMPACT STATEMENT: What is already known on this subject? There are recent case studies that report premature ovarian insufficiency (POI) following a post-vaccination autoimmune response against the HPV vaccine. These studies suggest that the possible trigger for the immune reaction might be the immunogen content of the vaccine. However, the number of clinical studies investigating the effects of the HPV vaccine on reproductive function and in vitro fertilisation outcomes is limited. What do the results of this study add? In contrast to the case reports suggesting impaired reproductive and ovarian functions in HPV vaccinated patients, this study finds that in IVF patients HPV vaccinated and non-vaccinated women have similar EYR, MII, 2PN, oocyte counts, fertilisation rates, positive, clinical and ongoing pregnancy rates. What are the implications of these findings for clinical practice and/or further research? The results suggest the HPV vaccine does not have a negative impact on embryo yielding rates oocyte counts and fertilisation rates, positive, clinical and ongoing pregnancy rates in IVF treatments. Hence, they can be safely used for primary prevention against cervical cancer.